Comprehensive analyses of genetic diversities and population structure of the Guizhou Dong group based on 44 Y-markers - Zhang,Hongling; Huang,Xiaolan; Jin,Xiaoye; Ren,Zheng; Wang,Qiyan; Yang,Meiqing; Xu,Ronglan; Yuan,Xiang; Yang,Daiquan; Liu,Hongyan; Shen,Wanyi; Zhang,Huiying; et al. (PeerJ, 2023)
Background The non-recombining region of the human Y chromosome (NRY) is a strictly paternally inherited genetic marker and the best material to trace the paternal lineages of populations. Y chromosomal short tandem repeat (Y-STR) is characterized by high polymorphism and paternal inheritance pattern, so it has been widely used in forensic medicine and population genetic research. This study aims to understand the genetic distribution of Y-STRs in the Guizhou Dong population, provide reference data for forensic application, and explore the phylogenetic relationships between the Guizhou Dong population and other comparison populations. Methods Based on the allele profile of 44 Y-markers in the Guizhou Dong group, we estimate their allele frequencies and haplotype frequencies. In addition, we also compare the forensic application efficiency of different Y-STR sets in the Guizhou Dong group. Finally, genetic relationships among Guizhou Dong and other reference populations are dissected by the multi-dimensional scaling and the phylogenetic tree. Results A total of 393 alleles are observed in 312 Guizhou Dong individuals for these Y-markers, with allele frequencies ranging from 0.0032 to 0.9679. The haplotype diversity and discriminatory capacity for these Y-markers in the Guizhou Dong population are 0.99984 and 0.97440, respectively. The population genetic analyses of the Guizhou Dong group and other reference populations show that the Guizhou Dong group has the closest genetic relationship with the Hunan Dong population, and followed by the Guizhou Tujia population. Conclusions In conclusion, these 44 Y-markers can be used as an effective tool for male differentiation in the Guizhou Dong group. The haplotype data in this study not only enrich the Y-STR data of different ethnic groups in China, but also have important significance for population genetics and forensic research.
Keywords: Guizhou Dong; Forensic features; Population genetics; STR; Y-chromosome